2018
DOI: 10.1159/000488679
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in the Genetics of Schizophrenia

Abstract: The last decade brought tremendous progress in the field of schizophrenia genetics. As a result of extensive collaborations and multiple technological advances, we now recognize many types of genetic variants that increase the risk. These include large copy number variants, rare coding inherited and de novο variants, and over 100 loci harboring common risk variants. While the type and contribution to the risk vary among genetic variants, there is concordance in the functions of genes they implicate, such as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(56 citation statements)
references
References 176 publications
(176 reference statements)
0
54
1
Order By: Relevance
“…This issue has become even more important with the revelation that the vast majority of neuropsychiatric disease-related single-nucleotide polymorphisms (SNPs) occur in non-coding regions (Avramopoulos, 2018). Due to chromosomal looping, the genes most linearly-proximal to a given variant are often not those directly affected (Mitchell et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…This issue has become even more important with the revelation that the vast majority of neuropsychiatric disease-related single-nucleotide polymorphisms (SNPs) occur in non-coding regions (Avramopoulos, 2018). Due to chromosomal looping, the genes most linearly-proximal to a given variant are often not those directly affected (Mitchell et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…0.37) [9, 10] and polygenic inheritance [11, 12]. However, promis ing genetic risk candidates for SCZ and MDD had not been well implicated until the emergence of recent large-scale genome-wide association studies (GWAS) [13-21]. GWAS is believed to be an ideal approach for studying common genetic variations across the genome, given its key feature that no a priori hypotheses are established [22].…”
Section: Introductionmentioning
confidence: 99%
“…Schizophrenia is a highly heritable disorder and it affected about 1% of the population worldwide ( Sullivan et al, 2003 , p. 20; Henriksen et al, 2017 ; Avramopoulos, 2018 ; Weinberger, 2019 ). Twins studies suggested the heritability is around 80% ( Sullivan et al, 2003 ; Henriksen et al, 2017 ; Avramopoulos, 2018 ) and common variants contributed to up to half of the genetic risk of schizophrenia ( International Schizophrenia Consortium et al, 2009 ; The Schizophrenia Psychiatric Genome-Wide Association Study (Gwas) Consortium, 2011 ). Genome-wide association studies (GWAS) identified more than 180 loci that were associated with the risk of schizophrenia ( Ripke et al, 2014 ; Li et al, 2017 ; Pardiñas et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%